Competences of South African midwifery educators: a transformative framework - Bekker, Elgonda Eritzema (University of the Free State, 2020)
Midwifery educators’ competencies are a crucial component in strengthening midwifery education and maternal healthcare. Moreover, quality midwifery education is fundamental in reaching universal health coverage by 2030. In this research, a transformative paradigm with the focus on gender inequality as the social justice element, enhanced by theoretical perspectives from feminism and social constructionism, was followed. A concurrent mixed-method design was deemed most appropriate to answer the research question: ”How can midwifery educators’ competencies best be strengthened to transform midwifery education in South Africa?” Competence strengths were defined and discovered, dreams were expressed, and the designed destiny framed during an Appreciate Inquiry session. The strengths-based approach was integrated with a realistic view of South African midwifery educators’ competencies gained by the self-administered WHO Midwifery Educator Core Competency Gap Analysis Tool. After analysis of the separate data sets, inference of the findings in triangulation with literature culminated in a transformative framework, which was refined by experts in maternal healthcare and midwifery education through a non-consensus Delphi. The meaning of all the contributions from the different perspectives of the interprofessional stakeholders were incorporated to strengthen the framework, thus taking a dialectic stance. The transformative framework consists of consecutive building blocks. Compliance with global standards for midwifery education, regulation and essential competencies forms the foundation. An enabling environment is the next element that facilitates national capacity building to address gaps in midwifery educators’ competence. Supported by the building blocks, midwifery education competence could ultimately improve the quality of midwifery care. The context of midwifery, including education, is framed by four elements emanating from a feminist approach, resulting in agency for midwives and women. This agency contributes to empowerment of women and decolonisation of midwifery, aimed at knowledge democracy. The transformative framework is presented to strengthen midwifery educators’ competencies and transform midwifery education in South Africa.
Thesis (Ph.D.(Nursing))--University of the Free State, 2020
Keywords: Midwifery educators; Midwives -- South Africa -- Practice; Maternity nursing